Characterization On The Mechanical And Physical Properties Of Chicken Skin Gelatin Films In Comparison To Mammalian Gelatin Films - Suderman N.; Isa M.I.N.; Sarbon N.M. (IOP Publishing Ltd, 2024)
The purpose of this study was to investigate the mechanical and physical properties of chicken skin gelatin film as compared to mammalian gelatin films in terms of tensile strength (TS), elongation at break (EAB), puncture force, water vapour permeability (WVP), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), light barrier, thermal properties and microstructure. Three film formulations using 4g gelatin of three different types (chicken skin, bovine, and porcine gelatin) and 1.5g glycerol were prepared under mechanical stirring at a temperature of 45˚C. The use of different types of gelatin resulted in different mechanical and physical properties. Results revealed that chicken skin gelatin film was optimal due to its high tensile strength (5.57 MPa) and low WVP (1.29 x 10-9 kPa) rate as compared to bovine and porcine gelatin films. The carboxyl group was revealed to be stronger in FTIR assay for chicken skin gelatin film, while XRD revealed amorphous characteristics at a peak 2Ɵ=20º. These results contributed to its superior physical characteristics. These desirable characteristics mean that chicken skin gelatin film has remarkable potential as a biodegradable film material as compared to commercial gelatin. It may become a key preferred alternative for producing gelatin films for edible film purposes